Durable Disease Control in Primary Pulmonary Sarcomatoid Carcinoma Following Pneumonectomy - Cheng-Shiun Shiue; Chao-Chun Chang; Meng-Ta Tsai; Yu-Ning Hu (Diagnostics)
We report a 26-year-old male presenting with a chronic cough and hemoptysis. Imaging revealed a large hypermetabolic mass in the left lower lung with the invasion of adjacent great vessels. A biopsy confirmed sarcomatoid carcinoma, a rare and aggressive form of primary pulmonary sarcoma. Due to vascular involvement, the patient underwent preoperative bronchial artery embolization followed by left pneumonectomy with pulmonary arterioplasty via median sternotomy. Postoperative recovery was uneventful. A two-year follow-up CT showed no recurrence. Primary pulmonary sarcomas are extremely rare, accounting for only 0.013–0.4% of lung malignancies, and are often diagnosed late due to nonspecific symptoms. This case highlights the importance of timely imaging, multidisciplinary planning, and aggressive surgical management in achieving long-term disease control, even in cases with extensive vascular invasion.